1994
DOI: 10.1161/01.hyp.23.1_suppl.i20
|View full text |Cite
|
Sign up to set email alerts
|

Salt-regulating hormones in young normotensive obese subjects. Effects of saline load.

Abstract: To investigate whether the response of salt-regulating hormones to volume expansion is impaired in obese subjects, we assessed the effects of saline load (0.25 mL/kg.min.120 min) in 9 young, healthy, normotensive obese subjects (body mass index, > 30 kg/m2) and in 10 lean control subjects (body mass index, < 25 kg/m2) matched for age, gender, height, and mean blood pressure. Hematocrit, plasma renin activity (PRA), plasma aldosterone (PA), atrial natriuretic factor (ANF), and urinary sodium excretion (UNaV) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
1
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 21 publications
(13 reference statements)
6
52
1
1
Order By: Relevance
“…This is also supported by previous observations that hyperinsulinemic 22 or obese 23 subjects are more sensitive to sodium load because of reduced effect of atrial natriuretic peptide, 24 -26 partly attributable to an increased clearance in adipose tissue. 27,28 This may also relate to Nt-proBNP, but the importance of the natriuretic clearance receptor C for clearance of Nt-proBNP is unknown.…”
Section: Olsen Et Al Natriuretic Peptides and The Metabolic Syndromesupporting
confidence: 87%
See 1 more Smart Citation
“…This is also supported by previous observations that hyperinsulinemic 22 or obese 23 subjects are more sensitive to sodium load because of reduced effect of atrial natriuretic peptide, 24 -26 partly attributable to an increased clearance in adipose tissue. 27,28 This may also relate to Nt-proBNP, but the importance of the natriuretic clearance receptor C for clearance of Nt-proBNP is unknown.…”
Section: Olsen Et Al Natriuretic Peptides and The Metabolic Syndromesupporting
confidence: 87%
“…14,22-24 LV mass was considered as an unadjusted variable and also after traditional normalizations for body surface area (BSA). 4,23 LV mass/BSA partition values of 116 g/m 2 in men and 104 g/m 2 in women were used as the upper gender-specific normal 95% confidence intervals, as described previously. 4,15 Relative wall thickness (RWT) was calculated as 2ϫ end-diastolic PWT/LV internal dimension.…”
Section: Echocardiographymentioning
confidence: 99%
“…One published report suggested that obese subjects have relatively low levels of atrial natriuretic peptide, especially after a salt load (33). Increased aldosterone secretion could be explained by a direct effect of circulating insulin on the adrenal, an effect we have been unable to confirm (34).…”
Section: Discussioncontrasting
confidence: 59%
“…36 Obese subjects were reported to have delayed urinary sodium excretion and a blunted response of plasma ANP to saline load. 37 Weight loss induced by caloric restriction led to significant natriuresis and diuresis, together with an early increase of circulating ANP levels. 38 Dessi-Fulgheri et al 39 reported that after caloric restriction for 4 days in obese hypertensive patients, ANP infusion caused more profound diuresis, natriuresis, reduction of BP, than ANP infusion did before caloric restriction.…”
Section: Nps Changesmentioning
confidence: 96%